An ethnographic study of tertiary students greeting - Moyo, Sicelokuhle (Midlands State University, 2017)
This study is a close analysis of how gender, language, relationships affect the way tertiary students greet in Midlands State University Zvishavane Campus. Greetings are more than just a way of proclaiming one’s presence but an important phenomenon of any society. The way people greet reveals a lot about their identity, background and ethnicity. Moreover, the act is carried out differently from one individual to the other. The way people greet is mostly determined by the relationships that exist between the individuals concerned. Language is not just a communication, it is also a carrier of culture. It, therefore, plays a major role in greetings. Greetings should not be taken for granted as they communicate masses about an individual and society as a whole.